Spatial assessment of the economic housing units a case study of the urban housing developments in Davao City - Salarda, Keith David M. (2016)
The aim of this study is to maximize the use of the interior spaces of low-cost housing units through an adaptive design using modular furniture and movable interior panels. The rigid construction of the current low-cost housing units forces the low-income families to spend more money on renovating space thus reducing funds much needed for daily expenses. This study was conducted in seven (7) different economic subdivisions located in Davao City with thirty (30) respondents from each with a total of two hundred ten (210s) respondents. A key informant interview was conducted to gather data for the socio-demographic and economic profile as well as the activity profile. Unit layout mapping was then conducted to measure the interior spaces each unit. The data was then assessed using Pearson?s product-moment correlation to find significant relationships between the variables using SPSS. The study concluded that all of the subdivisions failed the minimum standards required for a habitable space enough for a 5-person house but residents are still satisfied with the current state of their houses because of a lack of options in the market. Further studies should be conducted to better understand the impact of using the new creative designs in the long run. All in all, the study explored possible solutions that might relieve the current problem of the housing market.